Biochar Alone Did Not Increase Microbial Activity in Soils from a Temperate Climate That Had Long-Term Acidity Stress - Dvořáčková, Helena; Dvořáček, Jan; Záhora, Jaroslav; Šimečková, Jana (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2022)
Biochar can increase the microbial activity of a soil and the seed yield of oilseed rape. We performed a field experiment to determine the effect of different doses of biochar and the impact of nutrient additions on microbial activity in soils with low pH (4.69). Different doses of biochar were applied to plots in 2016 (0 t/ha (control), 15 t/ha (B15), 30 t/ha (B30), or 45 t/ha (B45)), and fertilization was applied during 2019 (90 kg P/ha) and 2020 (50 kg N/ha, 80 kg P/ha, and 50 kg K/ha). Maize was grown in 2016, barley in 2017, maize in 2018, wheat in 2019, and winter oilseed rape in 2020. All analyses were carried out in 2020. Higher biochar doses led to reduced seed yield of oilseed rape and inhibition of microbial activity (cumulative soil respiration, dehydrogenase activity (DHA), and leaching of mineral forms of nitrogen). Notably, dehydrogenase activity was more than 60% lower in plots with the highest biochar dose. All doses of biochar increased the soil pH compared to the control (control: 4.51 +- 0.04, B15: 4.69 +- 0.04, B30: 5.06 +- 0.05, B45: 5.05 +- 0.04) but did not increase microbial activity or the seed yield of oilseed rape. Thus, application of biochar alone did not increase the seed yield of oilseed rape or soil microbial activities, although it did increase soil pH.
Keywords: nitrogen; soil enzymes; plot experiment; DHA; mineral nitrogen